Pages passed from hand tot hand : the hidden tradition of homosexual literature in English from 1748 tot 1914 - Mitchell, Mark; Leavitt, David (Boston : Houghton Mifflin Company, 1997)
Fonds Suzan Daniel (FSD)
Engels
Monografie